Constructing semi-fluorinated PDEAEMA-b-PBTFVBP-b-PDEAEMA amphiphilic triblock copolymer via successive thermal step-growth cycloaddition polymerization and ATRP. Issue 45 (29th September 2015) - Feng, Chun; Zhu, Chao; Yao, Wenqiang; Lu, Guolin; Li, Yongjun; Lv, Xuliang; Jia, Mingchun; Huang, Xiaoyu
Abstract : Amphiphilic triblock copolymers containing semi-fluorinated PBTFVBP and hydrophilic PDEAEMA segments were synthesized by the site transformation strategy. Abstract : A series of amphiphilic perfluorocyclobutyl-containing ABA triblock copolymers, PDEAEMA- b -PBTFVBP- b -PDEAEMA (DEAEMA: 2-(diethylamino)ethyl methacrylate; BTFVBP: 4, 4′-bis(1, 2, 2-trifluorovinyloxy)biphenyl), was synthesized through the site transformation strategy, combining thermal step-growth cycloaddition polymerization of BTFVBP and atom transfer radical polymerization (ATRP) of DEAEMA. A BTFVBP trifluorovinyl aryl ether monomer was first thermally polymerized to form a semi-fluorinated perfluorocyclobutyl aryl ether-based segment, followed by end functionalization for preparing a Br-PBTFVBP-Br macroinitiator bearing one ATRP initiating group at each end. ATRP of DEAEMA was initiated by Br-PBTFVBP-Br to afford four PDEAEMA- b -PBTFVBP- b -PDEAEMA triblock copolymers with relatively narrow molecular weight distributions ( M w / M n ≤ 1.42) via varying the feeding ratio of DEAEMA to the macroinitiator. The critical micelle concentration (cmc) of the obtained amphiphilic triblock copolymers was determined by fluorescence spectroscopy using N -phenyl-1-naphthylamine as a probe. Micellar morphologies were investigated by transmission electron microscopy. It was shown that such triblock copolymers could self-assemble into large compound micelles, vesicles, and bowl-shaped micelles in aqueous solution with different initial water contents and compositions.